-22+7c=-5(4c+6)

Simple and best practice solution for -22+7c=-5(4c+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -22+7c=-5(4c+6) equation:


Simplifying
-22 + 7c = -5(4c + 6)

Reorder the terms:
-22 + 7c = -5(6 + 4c)
-22 + 7c = (6 * -5 + 4c * -5)
-22 + 7c = (-30 + -20c)

Solving
-22 + 7c = -30 + -20c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '20c' to each side of the equation.
-22 + 7c + 20c = -30 + -20c + 20c

Combine like terms: 7c + 20c = 27c
-22 + 27c = -30 + -20c + 20c

Combine like terms: -20c + 20c = 0
-22 + 27c = -30 + 0
-22 + 27c = -30

Add '22' to each side of the equation.
-22 + 22 + 27c = -30 + 22

Combine like terms: -22 + 22 = 0
0 + 27c = -30 + 22
27c = -30 + 22

Combine like terms: -30 + 22 = -8
27c = -8

Divide each side by '27'.
c = -0.2962962963

Simplifying
c = -0.2962962963

See similar equations:

| 2x(2)+17x+35=0 | | 3x(9)=24 | | x/281=40/360 | | 2x+13-7+6x= | | -16=-3(6k+9) | | 23=2+8(r+5) | | -20=-9d-2d | | 4.2+7=2.8 | | 3p^2+24p=-105 | | 6x^2-13b=0 | | 3-3*6+3=-13 | | -6+8(1-2x)=27 | | 9y+8+7=-26 | | (x+5)2=(2x)2 | | -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 | | 13x+72= | | a-12+5=-12 | | 6-9n+5n=16-90 | | 9*x=88 | | x+45=6x | | 3(c-2)+8=6+c-4 | | 3x+1=3x+0 | | 2x+3y=155 | | 9.8.2x=96 | | 2z-6z=-25 | | 20=22-d | | -7(9-5a)=-23 |

Equations solver categories